f ( x ) = ( arcsin ( x ) ) 3 + ( arccos ( x ) ) 3
If the sum of the maximum and minimum values of the function f : R → R can be expressed as c a π b , where a , b and c are positive integers with a , c coprime, find a + b + c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did it by using the a 3 + b 3 identity, but our methods are essentially the same :) Amazing solution, as usual, and thanks for it ! Cheers!
Sir why did you assumed α ∈ [ − 2 π , 2 π ] ?
Log in to reply
It's by definition of inverse trig functions
Log in to reply
Excuse me, but isn't Arccos (x) defined in [0;pi]? Hence isn't the function defined in the intersection of the two domains [0,pi/2]? In this case we have the minimum at the same point but the maximum on 0 or pi/2. Thanks, I'm sorry for my bad english.
Log in to reply
@Davide Calza – You are right. But I defined α = arcsin x and β = arccos x .
Log in to reply
@Chew-Seong Cheong – Right, sorry for the stupid question, thinking about It one minute more, i've made a bad mistake! Thanks for the answer
α = arcsin x ∈ [ − 2 π , 2 π ]
Log in to reply
Thanks Miraj Shah and Chew-Seong Cheong !
Log in to reply
@Akshay Yadav – Sorry think I made the same mistake! Can you explain please Akshay?
As Usual Awesome! :)
Problem Loading...
Note Loading...
Set Loading...
Let arcsin x = α and arccos x = β , then we have:
{ sin α = x cos β = x ⇒ cos α = 1 − x 2 ⇒ sin β = 1 − x 2
⇒ sin ( α + β ) ⇒ α + β ⇒ β = sin α cos β + cos α sin β = x 2 + 1 − x 2 = 1 = 2 π = 2 π − α
Now, we have:
f ( x ) = α 3 + β 3 = α 3 + ( 2 π − α ) 3 = α 3 + ( 8 π 3 − 4 3 π 2 α + 2 3 π α 2 − α 3 ) = 8 π ( 1 2 α 2 − 6 π α + π 2 ) = 8 1 2 π ( α 2 − 2 π α + 1 2 π 2 ) = 2 3 π ( [ α − 4 π ] 2 + 4 8 π 2 ) for α = arcsin x ∈ [ − 2 π , 2 π ]
We note that f ( x ) > 0 and it is maximum when α = − 2 π and minimum, α = 4 π . Therefore, we have:
f m a x ( x ) f m i n ( x ) ⇒ f m a x ( x ) + f m i n ( x ) = 2 3 π ( [ − 2 π − 4 π ] 2 + 4 8 π 2 ) = 2 3 π ( 1 6 9 π 2 + 4 8 π 2 ) = 8 7 π 3 = 2 3 π ( [ 4 π − 4 π ] 2 + 4 8 π 2 ) = 3 2 π 3 = 8 7 π 3 + 3 2 π 3 = 3 2 2 9 π 3
⇒ a + b + c = 2 9 + 3 + 3 2 = 6 4